Development of questionnaires for quantitative medical research - Shah, Shamsul Azhar (Institute for Clinical Research, NIH, Malaysia, 2022)
In research, a questionnaire is an important instrument for collecting data. The quality of the questionnaire has an impact on data collecting success and, ultimately, on the study's objectives (s). The overall approach to developing four types of questionnaires for quantitative research is discussed in this book: (a) questionnaires for capturing facts or information, (b) questionnaires for evaluating knowledge, (c) questionnaires for measuring latent variables, and (d) questionnaires for screening or diagnosing a subject. This book is intended to be a quick reference for researchers who need to create a high-quality questionnaire for their survey research.